A novel method for the fabrication of porous calcium hexaluminate (CA6) ceramics using pre-fired CaO/Al2O3 pellets as calcia source. Issue 4 (March 2020) - Zhao, Fei; Ge, Tiezhu; Zhang, Lixin; Xu, Enxia; Gao, Jinxing; Liu, Xinhong
Abstract: Herein, porous calcium hexaluminate ceramics that contain pores exhibiting multiple morphologies were fabricated via in situ reaction sintering using α-Al2 O3 powders and pre-fired CaO/Al2 O3 pellets. The results indicated that the composition of the pre-fired CaO/Al2 O3 pellets significantly affected the pore morphology, reaction-diffusion mechanisms, sintering behaviour and properties of the porous CA6 ceramics. For the specimens containing low CaO/Al2 O3 -ratio (0.37) pellets, the main reaction occurred by solid state diffusion, i.e. ion diffusion through the solid reactant phase, which resulted in a slow process and low CA6 formation rate at an elevated sintering temperature. With higher CaO/Al2 O3 -ratio (0.57) pellets, large-sized pores were observed because of transient liquid phase diffusion during the sintering process. The transient liquid phase diffusion effect increased the porosity of the porous ceramics and promoted the formation of a large number of plate-like CA6 grains in the walls of the pores, enhancing their mechanical properties and high-temperature performance. The porous CA6 ceramics containing high CaO/Al2 O3 -ratio (0.57) pellets sintered at 1700 °C exhibited high open porosity (55.88%), low thermal conductivity and excellent high-temperature performance.